Pengaruh Kualitas Pelayanan dan Kepuasan Pasien BPJS Terhadap Citra Klinik Pratama Universitas Riau Sehati I - Syahrul Gunawan; Zulkarnain; Samsir (Jurnal EMT KITA, 2022)
Patient satisfaction is an important factor in evaluating quality services, to improve the quality of health services for BPJS Health participants, health services are no longer centered on hospitals or advanced health facilities, but must be organized according to his medical needs. This principle will focus on basic health services/basic health facilities, such as puskesmas/clinics, which will become the main way for BPJS Health participants to get health services. This is the reason why this research was carried out. Where this research aims to analyze the effect of service quality and patient satisfaction BPJS on clinical image pratama Universitas Riau sehati 1. The method in this research is quantitative with conducted a survey of 96 samples of BPJS patients. The results of this study are: 1. Quality services provided by the clinic affect the satisfaction of BPJS patients with influence path coefficient value (ρ yx) 0.598. 2. BPJS patient satisfaction affects the image clinic of (ρ zy) 0.650. 3. The quality of service affects the clinical image by (ρzx) 0.172. The Primary Clinic of Riau Sehati 1 University has a positive image in the eyes of BPJS patients for providing their best service.